Incidencia del planeamiento operativo en la disminución del riesgo de informe de auditoría en la EDPYME Credivisión - Zapata Leon, David Giovani (2019)
ABSTRACT Planning is fundamental in the development of any activity to be undertaken, an action that is not alien to the development of an audit, so identifying the problem areas often leads to determine more time and resources than expected. The objective of this research is to determine the relationship between operational planning and the efficiency of the audit report of the Edpyme Credivisión. For the development of this work, the annual plan of the Internal Audit Unit of Edpyme Credivisión has been taken as a sample. The contrast design used was the nonexperimental design - transversal. The techniques used for data collection were observation, interview, flow chart and documentary analysis. With respect to the Operational Planning relationship and the efficiency of the Audit Report of the Edpyme Credivisión, for a determined period of time, the operational plan of the Internal Audit Unit will be evaluated, as well as its planning phase, as well as the audit reports presented by the Internal Audit Management to the Superintendency of Insurance Banking and AFP.